2022
DOI: 10.1016/j.cllc.2021.09.001
|View full text |Cite
|
Sign up to set email alerts
|

An Extensive-stage Small-cell Lung Cancer Case With Preexisting Lambert-Eaton Myasthenic Syndrome Successfully Treated With an Immune Checkpoint Inhibitor

Abstract: Immune checkpoint inhibitor (ICI) therapy could exacerbate preexisting active autoimmune diseases (AIDs), and the presence of preexisting AIDs might be associated with a greater risk of developing new immunerelated adverse events (irAEs).• The safety of ICIs for patients with Lambert-Eaton myasthenic syndrome (LEMS), a neuromuscular autoimmune disease known as a paraneoplastic syndrome mainly associated with small-cell lung cancer (SCLC), is fully unknown.• We experienced an extensive-stage (ES)-SCLC patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Among these three cases, LEMS improved by combination immunotherapy in two Japanese cases, but deteriorated by ICI monotherapy in the other German case. Our case was very similar in clinical course, treatment regimen and outcomes to the other Japanese case by Sakaguchi et al [ 8 ]. The difference between these two Japanese cases was ICI drug, i.e., durvalumab vs. atezolizumab.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Among these three cases, LEMS improved by combination immunotherapy in two Japanese cases, but deteriorated by ICI monotherapy in the other German case. Our case was very similar in clinical course, treatment regimen and outcomes to the other Japanese case by Sakaguchi et al [ 8 ]. The difference between these two Japanese cases was ICI drug, i.e., durvalumab vs. atezolizumab.…”
Section: Discussionsupporting
confidence: 84%
“…Then, she could continue chemotherapy without pembrolizumab. On the other hand, ours and the other two cases introduced ICIs soon after the confirmed diagnosis of malignancy and worsening LEMS [ 8 , 10 ]. Among these three cases, LEMS improved by combination immunotherapy in two Japanese cases, but deteriorated by ICI monotherapy in the other German case.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our institution experience was that IVIg was applied in acute phase to neutralize antibody for 5–7 days. Sakaguchi et al reported an extensive stage SCLC patient complicated with LEMS successfully treated by immune checkpoint inhibitor plus chemotherapy without a flare-up of LEMS [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…To summarize, in most cases treatment of the tumor reduced the LEMS-associated symptoms but none of these cases received treatment with avelumab. Some other case reports raises the concern regarding whether immunotherapy may cause LEMS (28)(29)(30)(31)(32), none of these are reported having MCC. The majority of the cases described had lung cancer and out of the case reports one cannot say whether LEMS was caused by the immunotherapy, only that it presented after initiation of treatment.…”
Section: Discussionmentioning
confidence: 99%